A smart glove with integrated triboelectric nanogenerator for self-powered gesture recognition and language expression. Issue 1 (31st December 2019) - Chiu, Che-Min; Chen, Shuo-Wen; Pao, Yu-Ping; Huang, Ming-Zheng; Chan, Shuen-Wen; Lin, Zong-Hong
ABSTRACT: Flexible electronics with great functional characteristics have proved to be a stepping stone in the field of wearable devices. Amongst all, gesture-sensing techniques have been widely studied for human-machine interfaces. In this paper, we propose a self-powered gesture-sensing system attached to the back of the hands, which has the capability of distinguishing hand gestures by measuring the triboelectric nanogenerator output signal. By attaching the sensor on the back of the hand, we can sense the displacement of tendons to detect the gestures. In addition, humidity resistance and durability of the device were tested and validated. Furthermore, we have established a set of rules to define the relationship between gestures and corresponding English letters. Therefore, the proposed sensor can further serve as an electronic sign language translator by converting gestures into words. Finally, we can integrate this system into gloves to enhance the applicability and utility. Overall, we have developed a real-time self-powered back-of-hand sensing system which can recognize various hand gestures. GRAPHICAL ABSTRACT: uf0001